Effect of Land Area, Production Amount, Cost and Price on the Income of Vaname Shrimp Pond Farmers in Malaha Village, Samaturu District, Kolaka Regency - Saleh, Melyana; Kartomo, Kartomo; Syaiful, Muhammad (PT. Riset Press International, 2024)
This study aims to determine the effect of land area, amount of production, cost and price partially and simultaneously on the income of vaname shrimp pond farmers in Malaha Village, Samaturu District, Kolaka Regency. This research method uses quantitative methods and data analysis methods using multiple linear regression analysis. The results of the study in the partial test showed that Land Area had a positive and partially significant effect on the Income of Pond Farmers with a value of Tcalculate (5,154) > Ttable (2,030), Total Production had a positive and significant partial effect on the Income of Pond Farmers with a value of Tcalculate (8,802) > Ttable (2,030), Cost had a negative and partially significant effect on the Income of Pond Farmers with a value of Tcalculate (2,837) > Ttable (2,030), and Price has a positive and partially significant effect on the Income of Pond Farmers with the value of Tcalculate (3,094) > Ttable (2,030). Meanwhile, the simultaneous test shows that Land Area, Production Amount, Cost, and Price have a significant effect simultaneously or together on the Income of Pond Farmers with a value of Fcalculate (119.172) > Ftable (2.63).